A highly robust control scheme design approaches for electric vehicles - Soh, Wei Bin (Nanyang Technological University, 2023)
With the rising of the EVs, the Permanent Magnet Synchronous Machines (PMSM) are gaining popularity in a wide range of industrial applications due to their high torque, low torque ripple, high efficiency, and high dynamic performance. A study on robust control scheme using Permanent Magnet Synchronous Motor (PMSM) is presented in this report. The main focus will be on developing of A Highly Robust Control Scheme Design Approaches for Electric Vehicles, with the proposed of Finite Control Set - Model Predictive Torque Control (FCS-MPTC) that features three robust controller such as the First Order Sliding Mode Observer, Second Order Super Twisted Observer - Sliding Mode Observer (STO-SMO) and lastly Third Order Extended State Observer (3_ESO). The robust control scheme will then be implemented in MATLAB/Simulink with each robust controller serving as a system overall observer. It will be place into a series of test to evaluated for its capabilities to achieve high performance, robustness, and uncertainty. Based on the simulation findings, adopting 3_ESO as the overall system observer is preferred over SMO and STO-SMO. With the proposed of robust control schemes being developed, they are geared toward in enhancing the performance and stability of electric vehicles while also ensuring their outstanding performance and robustness. The proposed overview of the entire system and its elements which include the robust control scheme, and the PMSM.